EVALUATION OF CHEMICAL SOIL DEGRADATION IN THE MUSYAB PROJECT USING OF THE FUZZY LOGIC IN GEOGRAPHIC INFORMATION SYSTEM - & Hamad, Abdulsada (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to use the fuzzy logic to employ complex and non-simple models to simple and understandable models that are concerned with no accuracy in the event or the concept itself in the GIS environmental to produce soil degradation maps of the chemical degradation for lands by spatial interpolation method (Inverse Distant Weight). The study area was selected in the province of Babil and within the large Musaaib project. Forty (40) surface samples and 12 profiles were drilled (soil profile). The chemical properties of the soil were then estimated. The results indicated that there were four types of chemical deterioration of the soil, which was characterized by a slight degradation of D1 with an area estimated at 1982.34ha, second class D2 represents the moderate degradation  which occupies an area of ​​1074.71ha while the third class Severe degradation D3 area is estimated at 2403.18hectares, while the fourth class very severe degradation D4 area of ​​2830.56hectares.